2017
DOI: 10.1182/bloodadvances.2017007187
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells in hemorrhagic shock: a critical role for glutaminolysis in fueling alanine transamination in rats

Abstract: Key Points• In vivo tracing of 13 C 15 N-glutamine reveals that glutaminolysis is an essential contributor to RBC metabolism following HS.• Inhibition of glutaminolysis impairs transamination reactions and GSH synthesis, promoting early mortality in hemorrhaged rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Similarly, RBC levels of some carboxylic acids (e.g., malate, 2-hydroxyglutarate) were higher in humans, whereas others (e.g., citrate, α-ketoglutarate, succinate, oxaloacetate, itaconate) were higher in RM ( Figure 5B ), suggesting species-specific differences in transamination reactions (e.g., those dependent on the activity of alanine and aspartate aminotransferases) or carboxylic acid metabolism via cytosolic isoforms of Krebs cycle enzymes, all of which are active in mature RBC. 34 , 36 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, RBC levels of some carboxylic acids (e.g., malate, 2-hydroxyglutarate) were higher in humans, whereas others (e.g., citrate, α-ketoglutarate, succinate, oxaloacetate, itaconate) were higher in RM ( Figure 5B ), suggesting species-specific differences in transamination reactions (e.g., those dependent on the activity of alanine and aspartate aminotransferases) or carboxylic acid metabolism via cytosolic isoforms of Krebs cycle enzymes, all of which are active in mature RBC. 34 , 36 38 …”
Section: Resultsmentioning
confidence: 99%
“…35 Consistent with dysregulation of purine oxidation and salvage, species-specific changes in aspartate (higher in RMs) and fumarate (higher in humans) levels were noted, suggesting a decreased rate of salvage reactions in RM RBCs (Figure 5B). Similarly, RBC levels of some carboxylic acids (e.g., malate, 2-hydroxyglutarate) were higher in humans, whereas others (e.g., citrate, alphaketoglutarate, succinate, oxaloacetate, itaconate) were higher in RMs (Figure 5B), suggesting species-specific differences in transamination reactions (e.g., those dependent on the activity of alanine and aspartate aminotransferases) or carboxylic acid metabolism via cytosolic isoforms of Krebs cycle enzymes, all of which are active in mature RBCs 34,[36][37][38] .…”
Section: Species-specific Differences In Metabolic Phenotypes Of Stormentioning
confidence: 99%
“…Fresh baboon RBCs also have a similar lifespan to humans (∼100 days) (Valeri et al, 2002), and hydrogen peroxide-damaged baboon RBCs have increased levels of spectrin-hemoglobin complexes facilitating more rapid removal from circulation (McKenney et al, 1990). Further, RBCs in both humans and baboons respond to altitude (D'Alessandro et al, 2016) or hemorrhagic hypoxia (Reisz et al, 2017) by promoting synthesis of 2,3-diphosphoglycerate, thereby enhancing hemoglobin transition state responsiveness to pH and carbon dioxide; this process promotes hemoglobin's T state conformation (right shift of the hemoglobin oxygen-dissociation curve), oxygen off-loading, and restoration of tissue oxygen homeostasis (Herman et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…RBC metabolism thus mirrors systemic metabolic homeostasis and its pathological derangements beyond traditional RBC-specific pathologies, such as sickle cell disease 5 (eg, HbA1c and diabetes). 1 More recently, it has been suggested that RBC metabolism might mirror acute (eg, hemorrhagic shock 6 or physical activity 7 ) and/or chronic metabolic aberrations, such as in aging 4 and inflammation. 7 Trisomy 21 (T21) is the etiological factor of Down syndrome (DS), the most common chromosomal abnormality in the human population, occurring in 1 in ;700 live births in the United States.…”
Section: Introductionmentioning
confidence: 99%